2021
DOI: 10.2147/ott.s282367
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Feedback Loop Between NAMPT and TGF-β Signaling Pathway in Colorectal Cancer Cells

Abstract: Background: Nicotinamide phosphoribosyltransferase (NAMPT) and the transforming growth factor-β (TGF-β) signaling pathway play important roles in colorectal tumorigenesis and progress. However, the underlying regulatory mechanisms between NAMPT and TGF-β signaling in colorectal cancer (CRC) remain poorly understood. Methods: Public data were extracted from the Oncomine database and the PrognoScan database to investigate the mRNA expression and the prognostic value of NAMPT, respectively, in CRC. Western blot t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…For example, CTSD, which is highly expressed in CRC tissues, is closely associated with a poor prognosis by promoting β-catenin pathway (Ding et al, 2022). Moreover, NAMPT is overexpressed in CRC tissues and is associated with a poor prognosis by stabilizing the protein components of Smad2, Smad3, and Smad4 in the TGF-β signaling pathway, thereby increasing the activity of the TGF-β signaling (Lv et al, 2021). S100A8 promotes CRC metastasis by increasing epithelialmesenchymal transition and promoting the TGF-β signaling pathway Frontiers in Genetics frontiersin.org (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CTSD, which is highly expressed in CRC tissues, is closely associated with a poor prognosis by promoting β-catenin pathway (Ding et al, 2022). Moreover, NAMPT is overexpressed in CRC tissues and is associated with a poor prognosis by stabilizing the protein components of Smad2, Smad3, and Smad4 in the TGF-β signaling pathway, thereby increasing the activity of the TGF-β signaling (Lv et al, 2021). S100A8 promotes CRC metastasis by increasing epithelialmesenchymal transition and promoting the TGF-β signaling pathway Frontiers in Genetics frontiersin.org (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…VEGFA-VEGFR2 Signaling Pathway [27], TGF-beta Signaling Pathway [24], Negative regulation of NOTCH4 signaling. There is already evidence that morphine promotes tumorigenesis and cetuximab resistance through EGFR signal activation in human colorectal cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…such as Cell cycle, DNA replication, P53 Signaling pathway [17], and VEGF Signaling pathway [18], were enriched in high NMB phenotypes. KEGG signaling pathways were enriched in low NMB phenotypes, including Colorectal cancer, ERBB Signaling pathway [19], JAK-STAT Signaling pathway [20], MAPK Signaling pathway [21], MTOR Signaling pathway [22], NOTCH Signaling pathway [23], pancreatic cancer, pathways in cancer, TGF-BETA Signaling pathway [24], and WNT Signaling pathway [25].…”
Section: Discussionmentioning
confidence: 99%
“…The literature review revealed that the vast majority of the identified genes had previously been linked to colorectal cancer pathogenesis. Of these genes, the ones that seem to have an important role in CRC are EZH2, PTEN, EGFR, IGF1, HGF, SMAD4 and PTGS2 [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: In Silico Analysis Of Crc Exosomal Lncrna/circrna–mirna–targ...mentioning
confidence: 99%